Evaluating students’ performance in mathematics and other subjects using fixed and individual control chart grading methods - Deogratias, Emmanuel; Rao, Gadde S.; Alphonce, Filbert (Journal of Mathematics and Science Teacher, 2024)
This paper focuses on evaluating students’ performance in mathematics and other subjects using fixed and individual control chart grading methods. This quantitative study involved 240 students and conducted in ordinary secondary schools in the Mbulu district. Minitab statistical software was used to analyze collected students’ performance by comparing fixed grading method with individual control charts grade. The findings revealed that a large number of students performed well using individual control chart than the fixed grading method. The findings imply that individual control chart grade was higher and practical method in evaluating students’ performance because of lowering the cut-off point of the performance for the individual student. Therefore, school teachers can use individual control chart grading method for improving individual student performance in each subject.